Microstructure and Composition of Hardened Paste of Soda Residue-Slag-Cement Binding Material System - Song, Rongjie; Zhao, Qingxin; Zhang, Jinrui; Liu, Jizhong (Frontiers in Materials, 2019)
In order to utilize industrial waste soda residue, a kind of binding material system based on soda residue-slag-cement has been developed. The microstructure and composition of hardened paste of the binding material system after curing for 28 days was analyzed by means of scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD) and thermogravimetric-differential scanning calorimetry (DSC-TG). The main hydration products of binding material system after curing for 28 days were C-S-H gel and 3CaO·Al2O3·CaCl2·10H2O crystal (Friedel’s salt) with a needle bar and irregular shape. The Ca/Si ratio of C-S-H gel in hydration products varied from 0.7 to 1.4, the ratio of n(Cx-S-Hy)/n(3CaO·Al2O3·CaCl2·10H2O) varied in the range of 1.8~6.4. The C-S-H gel and Friedel’s salt constituted the main strength source of the whole soda residue-slag-cement binding material system.